2015
DOI: 10.1186/s12986-015-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase is required for the anti-adipogenic effects of alpha-linolenic acid

Abstract: Backgroundn-3 long chain polyunsaturated fatty acid (n-3 LC PUFA) increases β-oxidation and limits lipid accumulation in adipocytes. The current study was conducted to determine whether their precursor alpha-linolenic acid (ALA) could also exert the above effects and how AMP-activated protein kinase (AMPK) was involved.MethodsAMPKα1−/−, AMPKα2−/− mice and wild-type (WT) mice were fed a high-fat diet (HFD) or HFD with ALA. Body weight was recorded weekly and serum was collected. Adipocytes size and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Adipocyte cell sizes in the adipose tissue were measured as described previously [41]. Briefly, images were captured using a light microscope (Olympus, Center Valley, PA, USA) equipped with a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…Adipocyte cell sizes in the adipose tissue were measured as described previously [41]. Briefly, images were captured using a light microscope (Olympus, Center Valley, PA, USA) equipped with a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…The adenosine monophosphate-activated protein kinase (AMPK) is a principal energy sensor, defined as a protein kinase activated by an increase in the AMP/ATP energy ratio [14]. The AMPK is also a heterotrimeric enzyme that plays a master role in energy homeostasis of adipose tissue [15], and is associated with the regulation of C/EBPα and PPARγ [16]. In addition, SREBP1 is also negatively regulated by AMPK [17].…”
Section: Introductionmentioning
confidence: 99%
“…So it can be supposed that AMPK can lower the expression of inflammatory proteins such as TNF α as well as other proteins involved in fatty acid synthesis. Recently, Zhou et al [ 42 ] demonstrated that the antiadipogenic effects of alpha-linolenic acid were dependent on AMPK and that its effects were abolished in AMPK α 1 and AMPK α 2 KO mice. In addition, the activation of AMPK by AICAR and metformin increases the activity of SOD.…”
Section: Discussionmentioning
confidence: 99%